Identification and Functional Analysis of Mutations in the Hypocretin (Orexin) Genes of Narcoleptic Canines - Hungs, Marcel; Fan, Jun; Lin, Ling; Lin, Xiaoyan; Maki, Richard A.; Mignot, Emmanuel

(untitled) (Genome Research, 2001)
Narcolepsy is a sleep disorder affecting animals and humans. Exon skipping mutations of the Hypocretin/Orexin-receptor-2 (Hcrtr2) gene were identified as the cause of narcolepsy in Dobermans and Labradors. Preprohypocretin (Hcrt) knockout mice have symptoms similar to human and canine narcolepsy. In this study, 11 sporadic cases of canine narcolepsy and two additional multiplex families were investigated for possible Hcrt andHcrtr2 mutations. Sporadic cases have been shown to have more variable disease onset, increased disease severity, and undetectable Hypocretin-1 levels in cerebrospinal fluid. The canine Hcrtlocus was isolated and characterized for this project. Only one novel mutation was identified in these two loci. This alteration results in a single amino acid substitution (E54K) in the N-terminal region of the Hcrtr2 receptor and autosomal recessive transmission in a Dachshund family. Functional analysis of previously-described exon-skipping mutations and of the E54K substitution were also performed using HEK-293 cell lines transfected with wild-type and mutated constructs. Results indicate a truncated Hcrtr2 protein, an absence of proper membrane localization, and undetectable binding and signal transduction for exon-skipping mutated constructs. In contrast, the E54K abnormality was associated with proper membrane localization, loss of ligand binding, and dramatically diminished calcium mobilization on activation of the receptor. These results are consistent with a loss of function for all three mutations. The absence of mutation in sporadic cases also indicates genetic heterogeneity in canine narcolepsy, as reported previously in humans.